Protective effects of Lactobacillus plantarum strain against protein malnutrition-induced muscle atrophy and bone loss in juvenile mice. - Hyerim Park; Sung-Hee Kim; Kyung-Ah Lee (PLoS ONE)
Early-life malnutrition adversely affects nearly all organ systems, resulting in multiple physiological adaptations, including growth restriction and muscle and bone loss. Although there is growing evidence that probiotics effectively improve systemic growth under malnourished conditions in different animal models, our knowledge of the beneficial effects of probiotics on various organs is limited. Here, we show that Lactobacillus plantarum strain WJL (LpWJL) can mitigate skeletal muscle and bone loss in protein-malnourished juvenile mice. Mice on prenatal day 21 were fed a protein-malnourished (P-MAL) diet with or without LpWJL supplementation for six weeks. Compared to mice on the P-MAL diet alone, LpWJL supplementation significantly increased muscle mass and size, resulting in enhanced muscle strength and endurance capacity. Furthermore, LpWJL supplementation induced the expression of the key growth factor IGF-1 while decreasing muscle atrophy markers such as Atrogin-1 and MuRF-1, indicating potential mechanisms by which protein malnutrition-induced muscle wasting is counteracted. Additionally, LpWJL supplementation alleviated the reduction in cortical bone thickness and the deterioration of trabecular bone microstructure in the femur. Taken together, these results indicate that LpWJL can protect against skeletal muscle atrophy and compromised bone microarchitecture caused by protein malnutrition, providing novel insights into the potential therapeutic applications of probiotics for treating malnutrition-related disorders.